2011
DOI: 10.1039/c1cp20990f
|View full text |Cite
|
Sign up to set email alerts
|

Measuring acetic acid dimer modes by ultrafast time-domain Raman spectroscopy

Abstract: Acetic acid is capable of forming strong multiple hydrogen bonds and therefore different dimeric H-bonded structures in neat liquid phase and in solutions. The low frequency Raman spectra of acetic acid (neat, in aqueous solution and as a function of temperature) were obtained by ultrafast time and polarization resolved optical Kerr effect (OKE) measurements. Isotropic OKE measurements clearly reveal a specific totally symmetric mode related to the dimeric structure H-bond stretching mode. The effects of isoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 36 publications
4
40
0
Order By: Relevance
“…This picture of a loosely associated, disordered cluster clicking into order may be speculative, but has been suggested before for the case of NaCl. 35 For NPLIN, we speculate that the energy gain provided by the electric field, which is present for the equivalent of thousands of intermolecular vibrational periods, 34 assists the cluster in finding a pathway to a lower energy configuration. If this is the case, the polarizability interaction should favour certain molecular configurations within the cluster, i.e., specific directions on the multidimensional potential energy surface.…”
Section: Resultsmentioning
confidence: 97%
“…This picture of a loosely associated, disordered cluster clicking into order may be speculative, but has been suggested before for the case of NaCl. 35 For NPLIN, we speculate that the energy gain provided by the electric field, which is present for the equivalent of thousands of intermolecular vibrational periods, 34 assists the cluster in finding a pathway to a lower energy configuration. If this is the case, the polarizability interaction should favour certain molecular configurations within the cluster, i.e., specific directions on the multidimensional potential energy surface.…”
Section: Resultsmentioning
confidence: 97%
“…[1][2][3][4][5] The lowest energy structure of carboxylic acid homodimers has two strong and equivalent O−H•••O=C hydrogen bonds, which yield the locally cyclic arrangement illustrated in Figure 1(a) for acetic acid (AA), and this cyclic structure is prevalent in the gas phase. 6,7 However, the crystalline state of AA is dominated by The structure of the liquid phase is still the subject of controversy, with some studies indicating a preponderance of cyclic dimers 10,11 whilst others favor segments of catemer chains, 12,13 potentially as short as the trimer. 14 Despite its important role as the repeating unit of the catemer structure, relatively little is known about the metastable AA dimer shown in Figure 1(c).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of solid PBMA show the presence of hydrogen bonding between carboxylic acid side chains [ 26 ]. It has only recently been shown that simple carboxylic acids, such as acetic and lactic acids, exist predominantly as cyclic hydrogen bonded dimers in aqueous solution rather than in other hydrogen bonded forms that can also involve water [ 27 , 28 ]. Therefore, study of PBMA in aqueous solution is expected to yield important evidence supporting the poly (β- D -malic acid) hypothesis.…”
Section: Introductionmentioning
confidence: 99%